Rab11 Regulates Trafficking of Trans-sialidase to the Plasma Membrane through the Contractile Vacuole Complex of Trypanosoma cruzi - Niyogi, Sayantanee (2014)
Trypanosoma cruzi is the etiologic agent of Chagas disease. Although this is not a free-living organism it has conserved a contractile vacuole complex (CVC) to regulate its osmolarity. This obligate intracellular pathogen is, in addition, dependent on surface proteins to invade its hosts. Here we used a combination of genetic and biochemical approaches to delineate the contribution of the CVC to the traffic of glycosylphosphatidylinositol (GPI)-anchored proteins to the plasma membrane of the parasite and promote host invasion. While T. cruzi Rab11 (GFP-TcRab11) localized to the CVC, a dominant negative (DN) mutant tagged with GFP (GFP-TcRab11DN) localized to the cytosol, and epimastigotes expressing this mutant were less responsive to hyposmotic and hyperosmotic stress. Mutant parasites were still able to differentiate into metacyclic forms and infect host cells. GPI-anchored trans-sialidase (TcTS), mucins of the 60–200 KDa family, and trypomastigote small surface antigen (TcTSSA II) co-localized with GFP-TcRab11 to the CVC during transformation of intracellular amastigotes into trypomastigotes. Mucins of the gp35/50 family also co-localized with the CVC during metacyclogenesis. Parasites expressing GFP-TcRab11DN prevented TcTS, but not other membrane proteins, from reaching the plasma membrane, and were less infective as compared to wild type cells. Incubation of these mutants in the presence of exogenous recombinant active, but not inactive, TcTS, and a sialic acid donor, before infecting host cells, partially rescued infectivity of trypomastigotes. Taking together these results reveal roles of TcRab11 in osmoregulation and trafficking of trans-sialidase to the plasma membrane, the role of trans-sialidase in promoting infection, and a novel unconventional mechanism of GPI-anchored protein secretion.